Pulsed laser deposited CuNb2O6 polymorph photocathode-An alternate to NiO p-DSSCs. (January 2021) - Sabari Girisun, T.C.; Priyadarshani, N.; Panda, Subhendu K.; Subramanian, B.
Abstract: Efficient photocathodes made of polymorph monoclinic and orthorhombic CuNb2 O6 thin films was prepared by PLD technique (248 nm, 5 Hz, 525 mJ/cm 2, (30 °C, 100 °C, 200 °C, 400 °C, 600 °C). Desired phase formation was confirmed from XRD peak corresponding to ( 1 ‾ 31) and (131) (d = 2.975 Å and d = 2.919 Å) of m-CuNb2 O6 and (311) (d = 2.939 Å) of o-CuNb2 O6 plane. Morphological analysis exposes transformation of cubic into truncated cubes in m-CuNb2 O6 and polyhedron to spherical particles in m-CuNb2 O6 thin films. Using CuNb2 O6, p-DSSC was fabricated (CNO/N719/ I − / I 3 − /Pt) and their efficiency was tested. Photovoltaic cell exhibited device performance of m-CuNb2 O6 (0.24%) and o-CuNb2 O6 (0.22%). Higher photovoltaic performance of o-CuNb2 O6 (600 °C) photocathode DSSC arises due to various factors like dense, continuous surface with well-connected morphology, higher dye loading, NIR light harnessing capability and higher photoconversion efficiency. PLD deposited CuNb2 O6 provides a new insight in the DSSCs application. Graphical abstract: Image 1 Highlights: New photocathodes made of polymorph (monoclinic and orthorhombic) CuNb2 O6 was prepared by PLD technique. Fabrication of p-DSSC with assembly CNO/N719/ I − / I 3 − /Pt was made. Influence of substrate temperature in altering the PV performance of p-DSSC was done. p-DSSC showed highest efficiency of 0.24% with optimized monoclinic CuNb2 O6 photocathodes.